Economic sanctions and agricultural trade - Larch, Mario; Luckstead, Jeff; Yotov, Yoto V. (American Journal of Agricultural Economics, 2024)
Economic sanctions are more popular than ever. But do they affect agricultural trade? Combining two new datasets and capitalizing on the latest developments in the empirical structural gravity literature, we investigate the effects of sanctions on international trade of agricultural products. We find that trade sanctions impede agricultural trade, whereas other sanctions do not show any significant impact. Complete trade sanctions have led to about a 67% decrease in the agricultural trade between the sanctioned and sanctioning countries, or a corresponding tariff equivalent of 25%, and we also obtain significant estimates for partial sanctions. At the industry level, we find substantial heterogeneity depending on the sanctioning and sanctioned countries, the type of sanctions used, and the direction of trade flows. The 2014 sanctions on Russia substantially decreased Russia's agricultural trade, mainly due to reduced trade with the EU but also due to reduced trade with other countries. Although no definitive evidence exists that sanctions alter the actions of governments of receiving countries, this paper provides broad evidence that sanctions hamper agrifood trade and hurt producers, consumers, and real output.
Keywords: Agriculture; Heterogeneity; Sanctions; Structural Gravity; Trade